2013
DOI: 10.1039/c3sm27767d
|View full text |Cite
|
Sign up to set email alerts
|

Graphene surface induced specific self-assembly of poly(3-hexylthiophene) for nanohybrid optoelectronics: from first-principles calculation to experimental characterizations

Abstract: We demonstrate a specific chain alignment of p-conjugated polythiophenes on the graphene monolayer via first-principles calculation and experimental characterizations. The effects of alkyl chain and thiophene backbone in poly(3-hexylthiophene) (P3HT) on the specific binding energy and molecular configuration on the graphene monolayer are independently investigated. Due to specific p-p interaction and van der Waals interaction between P3HT and graphene monolayer, two different configurations (edge-on and face-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 44 publications
3
35
0
Order By: Relevance
“…The 10 nm film deposited on graphene (Figure C) also shows strong (h00) alignment along z, but also exhibited a well defined (010) diffraction peak along the z axis, which is characteristic of π–π stacking perpendicular to the plane (face‐on in Figure A). This result is consistent with binding energy calculations performed between a P3HT chain and a graphene surface, which showed that face‐on orientation is favored at the surface of graphene …”
Section: Resultssupporting
confidence: 90%
“…The 10 nm film deposited on graphene (Figure C) also shows strong (h00) alignment along z, but also exhibited a well defined (010) diffraction peak along the z axis, which is characteristic of π–π stacking perpendicular to the plane (face‐on in Figure A). This result is consistent with binding energy calculations performed between a P3HT chain and a graphene surface, which showed that face‐on orientation is favored at the surface of graphene …”
Section: Resultssupporting
confidence: 90%
“…The crystallization kinetics of high‐density and low‐density polyethylenes on CNTs were also investigated by Depan et al . The induced crystallization of P3ATs onto graphenic materials was also widely reported; e.g. well‐oriented ultrathin P3HT films on graphene, a graphene oxide/P3AT mixture having semi‐spherulites, connecting the individual reduced graphene oxide (rGO) monolayers with P3HT nanowires 53 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Qu et al reported a reduced GO (rGO)‐pyrene‐PCBM composite, in which the PCBM was attached onto rGO via the non‐covalent functionalization approach and applied in P3HT:PCBM bulk heterojunction devices, affording a PCE of 3.89%. Suspensions of graphene and rGO have also been utilized to nucleate P3HT nanofibers and modify the orientation of crystals in P3HT thin films …”
Section: Introductionmentioning
confidence: 99%